Dark solitary pulses and moving fronts in an optical medium with the higher-order dispersive and nonlinear effects. (November 2022) - Triki, Houria; Sun, Yunzhou; Zhou, Qin; Biswas, Anjan; Yıldırım, Yakup; Alshehri, Hashim M.
Abstract: We study the propagation dynamics of extremely short light pulses in an optical fiber medium exhibiting a plethora of higher-order dispersive and nonlinear effects of different nature. The wave propagation in such nonlinear media is described by an extended nonlinear Schrö dinger equation incorporating both even and odd higher-order terms. We introduce an appropriate nonlinear equation which enables us to achieve analytical shape-preserved and periodic wave solutions for the model. A new dark solitary wave is identified for the first time in the presence of all physical processes. In addition, we show that moving fronts or optical shock-type soliton solutions exist for the considered model. The periodic wave solutions are also found together with the parametric conditions for their existence. Results in this study may be useful for experimental realization of shape-preserved pulses in optical fibers and further understanding of their optical transmission properties. Highlights: A variety of higher-order dispersive and nonlinear e§ects are considered. An extended NLSE incorporating both odd and even higher-order terms is studied. A novel class of exact dark solitary wave solutions. A novel class of exact dark solitary wave solutions is obtained.